1991
DOI: 10.1126/science.252.5010.1266
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Electrons to Structural Changes

Abstract: The properties of a molecule are determined by the distribution of its electrons. This distribution can be described by the charge density, which is readily obtained from the wave functions derived by ab initio molecular orbital calculations. The charge density may be analyzed in a number of different fashions to give information about the effects of substituents, structural changes, and electronic excitation on the properties of molecules; one common procedure makes use of projection density or charge differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 46 publications
3
45
0
Order By: Relevance
“…Kinetic parameters of rotaxanes with tetralactam wheels in comparison with those with sulfonamide wheels Furthermore, comparison of Rot3@2 and Rot4@2, studied under the same conditions, led us to the conclusion that hydrogen bonding does not play a significant role. Fourthly, rotational barriers (Scheme 6) in carbonamides have been studied intensely both experimentally [25] and theoretically [26] and are of the order of 80 kJ/mol, while those of sulfonamides have been calculated to amount to ca. 40 kJ/ mol.…”
Section: Tetralactam Wheel Versus Sulfonamide Macrocyclementioning
confidence: 99%
“…Kinetic parameters of rotaxanes with tetralactam wheels in comparison with those with sulfonamide wheels Furthermore, comparison of Rot3@2 and Rot4@2, studied under the same conditions, led us to the conclusion that hydrogen bonding does not play a significant role. Fourthly, rotational barriers (Scheme 6) in carbonamides have been studied intensely both experimentally [25] and theoretically [26] and are of the order of 80 kJ/mol, while those of sulfonamides have been calculated to amount to ca. 40 kJ/ mol.…”
Section: Tetralactam Wheel Versus Sulfonamide Macrocyclementioning
confidence: 99%
“…21). It has long been recognized that, due to the presence of electron lone pairs, polarization effects, and so on, the partial atomic charges obtained from different schemes can neither be thought as point charges [22] nor should the charges be considered to be uniformly distributed over atomic spheres. Over the past several years, studies of ESP surfaces have revealed many instances of positive regions falling within otherwise negative regions on the exposed potential surface maps [23].…”
Section: Introductionmentioning
confidence: 99%
“…In support of this reevaluation of resonance effects, recent calculational investigations have shown that only a small portion of allylic resonance energy can be attributed to charge delocalization [8]. This result does not imply that electron density and its associated kinetic energy does Anti Enaminonitrile TS not migrate from atom to atom during the course of a conformational change, but rather that the pathways involved in such charge and energy flow are often not those associated with canonical resonance forms.…”
Section: Introductionmentioning
confidence: 81%